1992
DOI: 10.1055/s-2007-1021257
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Cardiac Dimensions, Anthropometric Characteristics and Maximal Aerobic Power (V̇O2max) in Young Men

Abstract: Echocardiographic dimensions, anthropometric data and maximal oxygen uptake (VO2max) were studied in 26 healthy sedentary male controls (mean age, 22.0 yrs) and 15 male endurance athletes (mean age, 20.3 yrs). Athletes displayed significantly greater mean values for left ventricular internal dimension at end-diastole (LVIDd), end-diastolic volume (LVEDV) and left ventricular mass (LVM). Statistically significant positive correlations were observed within the sedentary control group between left ventricular end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
30
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 9 publications
5
30
0
Order By: Relevance
“…Since glucose uptake by PET is determined per volume of the heart muscle, reduced glucose uptake may reflect decreased need of energy per the volume of heart muscle. The left ventricular mass was substantially increased in the athletes as previously described (51,52), and it was increased in proportion to the physical fitness. Due to differences in heart size, total myocardial glucose uptake was similar in the two groups.…”
Section: Discussionsupporting
confidence: 54%
“…Since glucose uptake by PET is determined per volume of the heart muscle, reduced glucose uptake may reflect decreased need of energy per the volume of heart muscle. The left ventricular mass was substantially increased in the athletes as previously described (51,52), and it was increased in proportion to the physical fitness. Due to differences in heart size, total myocardial glucose uptake was similar in the two groups.…”
Section: Discussionsupporting
confidence: 54%
“…Postmortem examination of superlative athletes, both equine and human, have revealed substantially larger hearts than would have been predicted from lean body mass (20). The Fick principle and the dependence of cardiac output and thence O 2 uptake (V O 2 ) on stroke volume suggest that a relationship between relative heart size and athletic performance is likely (20), particularly as success in endurance competitions is inextricably linked to the ability of an individual to support a high V O 2 over prolonged periods (1,2,16). Nevertheless, despite a body of evidence supporting the concept that heart size and athletic performance are related, this hypothesis has not yet satisfactorily been proven in a population of athletes with a wide range of abilities.…”
mentioning
confidence: 99%
“…In order to compare to previous findings in men, Hedman et al [439] examined the relationship between cardiac dimensions and cardiac function to V O2max in a group of untrained women (n = 48) and a group of national and regional level female These findings are consistent with a previous study in female rowers [440] and young men [441] . The authors suggested that applying the approach of scaling cardiac dimensions by the appropriate power of body surface area may aid in future comparisons between male and female athletes, as this may prevent overand underestimating the influence of differences in body composition between sexes [439] .…”
Section: V O 2 Maxsupporting
confidence: 81%